Становлення і розвиток естрадно-вокального мистецтва в Китаї в 1910-60 рр. - Бойко, А. М. (ХДАК, 2017)
Розглянуто особливості становлення та розвитку естрадно-вокального мистецтва в Китаї впродовж 1910–60 рр. Визначено головні передумови, що суттєво вплинули на його формування. Надано загальну характеристику основних періодів зазначеного процесу. Висвітлено творчу діяльність видатних китайських митців (композиторів і виконавців) у царині вокально-естрадної музики.

The characteristic features of the formation and development of Chinese varietyvocal art in the period from 1910s to 1960s are revealed. The main prerequisites that had the greatest influence on its formation are defined. The general description of the main periods of the specified process is provided. The artistic activities of the famous Chinese artists (composers and performers) in the field of variety-vocal music are highlighted.
Keywords: музичне мистецтво Китаю; естрадно-вокальне мистецтво; Chinese music culture; Chinese vocal art; vocal performance